(untitled) (Zdravstveni glasnik, 2024)
Introduction: Stroke is by far the most frequent and significant neurological disease in adulthood. In transition countries such as Bosnia and Herzegovina, stroke is at the top of the mortality scale, together with heart diseases. Objective: Review the frequency of stroke in patients hospitalized at Clinic for Neurology, Clinical Centre of the University of Sarajevo (CCUS), to present their clinical-epidemiological characteristics, and point out to the importance of diagnostic methods and the identification of stroke risk factors. Subjects and methods: In this retrospective, descriptive and clinical-epidemiological study, data were collected in the period from 2013 to 2015. The study included 4258 hospitalized patients, with 1694 suffered from stroke. The study is based on the analysis of data from patients’’ medical histories. Results: The prevalent type of stroke was ischemic (84.5%, in average) while the most represented was thrombotic stroke (34.6% in average). Motor deficit is the leading symptom (61%), while arterial hypertension is the most represented (80.0%) factor of risk. The patients, at the most (72.4%), are the retired persons, most commonly (17.1%) sales persons as professional occupation recorded. Ischemic CVI is more common in patients from urban areas, while in patients from rural areas it is the hemorrhagic CVI. Complete independence with lighter consequences (62.0%) is the most common post incidence outcome, while death (50.0%) is the statistically significant outcome in patients with ischemic CVI with hemorrhagic transformation. Conclusion: The study reveals an evident escalation in the number of stroke patients pertinent to the aging, while the younger population is not being spared either. Despite the fact that the prevention is the best approach to stroke issue, there are high frequency of risk factors present.